THE INFLUENCE OF WORK OVERLOAD, INTELLECTUAL QUOTIENT, EMOTIONAL QUOTIENT, AND SPIRITUAL QUOTIENT ON THE PERFORMANCE OF EXTERNAL AUDITORS - Hakim, Luqman Nul; Arifah, Siti; Pramudyastuti, Octavia Lhaksmi (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
Along with the times and technology that is so fast requires everyone to improve their performance. One of them is the external auditor profession. This study aims to analyze the effect of work overload, intellectual quotient, emotional quotient, and spiritual quotient on the performance of external auditors. This study uses a quantitative method using primary data. The population used in this study is the Public Accounting Firm (KAP) in DKI Jakarta. The sample used a purposive sampling method with a total of 75 respondents who had the criteria of being worked as an auditor at KAP in DKI Jakarta with a minimum of 6 months of works. The results of this study indicate that work overload has a negative effect on the performance of external auditors while the intellectual quotient, emotional quotient, and spiritual quotient have a positive effect on the performance of external auditors